2019
DOI: 10.1063/1.5100282
|View full text |Cite
|
Sign up to set email alerts
|

Diindenoperylene thin-film structure on MoS2 monolayer

Abstract: Research on two-dimensional (2D) atomic crystals is one of the highly progressive topics in (opto)electronics, as the van der Waals (vdW) interactions enable integration of 2D crystals with a broad range of materials. Organic π-conjugated molecules offer new opportunities for creating the so-called “hybrid” vdW heterostructures, in which their anisotropy adds an extra degree of functional possibilities. Moreover, it was found that in the case of organic molecules, the 2D substrate changes the molecular orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…We fitted the intensity profiles of the diffraction peaks with a Gaussian function in both, q xy and q z directions, obtaining their reciprocal space positions. Employing the genetic algorithm as the fitting procedure, 44 the unit cell parameters were calculated. We found that NCOH molecules in a thin film are arranged in a monoclinic 9 structure (space group P2 1 /m) with the unit cell parameters: a = (8.4 ± 0.1) Å, b = (6.0 ± 0.1) Å, c = (21.1 ± 0.5) Å, and β = (99.6 ± 0.3)°, where the given errors include the error from the genetic algorithm calculations and the error induced by the broad sample area probed by the X-rays (~ 1 mm 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We fitted the intensity profiles of the diffraction peaks with a Gaussian function in both, q xy and q z directions, obtaining their reciprocal space positions. Employing the genetic algorithm as the fitting procedure, 44 the unit cell parameters were calculated. We found that NCOH molecules in a thin film are arranged in a monoclinic 9 structure (space group P2 1 /m) with the unit cell parameters: a = (8.4 ± 0.1) Å, b = (6.0 ± 0.1) Å, c = (21.1 ± 0.5) Å, and β = (99.6 ± 0.3)°, where the given errors include the error from the genetic algorithm calculations and the error induced by the broad sample area probed by the X-rays (~ 1 mm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37] On the other hand, a lying-down orientation of molecules is observed for strongly interacting substrates such as metals or twodimensional materials. 19,35,[38][39][40][41][42][43][44] We have chosen several substrates to study the crystallographic structure of NCOH that depends on a particular molecular orientation -Si substrate with a native oxide layer and two types of few-layer MoS 2 substrates with mutually perpendicular alignment of atomic layers.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the molecular orientation on a solid substrate is especially important in organic (opto)electronics, where the properties such as the charge-carrier lifetime, interfacial energetics, or the light absorption are strongly correlated with the anisotropic nature of molecules. GIWAXS study of thin DIP film on MoS 2 showed that DIP forms separate islands on the top of the MoS 2 monolayer with lying-down orientation of the molecules in a triclinic lattice [222]. GID study of planar-heterojunctions of molecular donor material α-sexithiophene with DIP acceptor molecules described structural difference, crystallinity, and the molecular orientation, in films grown at room and 100 • C [223] and linked them with the characteristic parameters of the corresponding OPV cells.…”
Section: Polymer Photovoltaicsmentioning
confidence: 97%
“…45,80 The molecular sizes for DIP in the high temperature bulk phase 80 give roughly the same unit cell parameters as the thin film phase. 82,83 The molecular sizes for the acceptors are taken from mixed crystals reported in literature 50,79 and compared to the single crystal data for F6CTNNQ. 41 Whereas DBTTF and the acceptors have quite similar sizes, DIP is larger along the long axis of the molecule.…”
Section: Paper Materials Advancesmentioning
confidence: 99%